Altered Visual Adaptation to Body Shape in Eating Disorders: Implications for Body Image Distortion. (July 2016) - Mohr, Harald M.; Rickmeyer, Constanze; Hummel, Dennis; Ernst, Mareike; Grabhorn, Ralph
Previous research has shown that after adapting to a thin body, healthy participants (HP) perceive pictures of their own bodies as being fatter and vice versa. This aftereffect might contribute to the development of perceptual body image disturbances in eating disorders (ED). In the present study, HP and ED completed a behavioral experiment to rate manipulated pictures of their own bodies after adaptation to thin or fat body pictures. After adapting to a thin body, HP judged a thinner than actual body picture to be the most realistic and vice versa, resembling a typical aftereffect. ED only showed such an adaptation effect when they adapted to fat body pictures. The reported results indicate a relationship between body image distortion in ED and visual body image adaptation. It can be suspected that due to a pre-existing, long-lasting adaptation to thin body shapes in ED, an additional visual adaption to thin body shapes cannot be induced. Hence this pre-existing adaptation to thin body shapes could induce perceptual body image distortions in ED.